Increasing mothers' reproductive health knowledge and attitudes through education on youth internet-based social interaction - Fitriana Putri Utami; Nur Syarianingsih Syam; Desi Nurfita (Jurnal Cakrawala Promkes, 2023)
Adolescents have the highest rate of internet usage compared to those of different ages. Dissertation media, societal changes, and insufficient parental involvement support the development of promiscuity in adolescents. Parents, especially mothers, have a strong role in controlling the behavior of adolescents. Therefore, mothers need to have good knowledge and attitudes related to youth internet-based social interaction. The goal of this study is to assess changes in mothers' attitudes and knowledge because of education regarding how young people engage online and how that affects their reproductive health.  Forms of adolescent sexual behavior, pornography, adolescent self-concept, cyberbullying, and parent-adolescent communication are among the knowledge and attitude topics that are evaluated. In this study, a one-group, quasi-experimental pretest-posttest approach was adopted. The research sample consists of 21 participants that were chosen using purposive sampling.  A paired t-test was utilized to assess the questionnaire data. In the pre- and post-test, the respondents’ average knowledge score rose from 95.23 to 97.14. P value of 0.428 (95% CI: 3.00–6.61). Respondents’ attitude score rose from 77.85 to 85.95 (95% CI: 1.56–14.63). These results indicated differences in the respondents’ attitudes before and after training but not in their knowledge, although both of them experienced an increase in average scores. Youth internet-based social interaction for mothers can improve mothers’ attitudes and knowledge. To avoid juvenile delinquency, a health program that involves parental involvement in disseminating information about reproductive health in connection to teenage social interaction is necessary.